FIRST RECORD OF Cantherhines multilineatus (TANAKA, 1918) (TETRAODONTIFORMES: MONACANTHIDAE) IN INDONESIA - Peristiwady, Teguh; Makatipu, Petrus; Takaendengan, K; Ahmad, Fasmi (Makara Journal of Science, 2010)
Two specimens of Cantherhines multilineatus were collected from Girian Fish Market, Bitung, North Sulawesi on January 7 and August 18, 2009. It was caught from depths of about 20–30 m in association with other coral reef fishes. In the world, this species is found in many scattered locations in the Western Indian Ocean, Eastern Indian Ocean, Northwest Pacific and Western Central Pacific and its distribution was reported from Taiwan and Japan. Its morphological features and diagnostic characters are discussed and illustrated